1960
DOI: 10.1111/j.1151-2916.1960.tb13674.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Magnesia Single Crystals Corn pression

Abstract: Stress-strain curves of single crystals of magnesia compressed in the [IOO] direction are reported at temperatures from -196' to 1200°C.; curves are also shown for different rates of loading at room temperature. The crystals show considerable ductility at all temperatures and at room temperature can be deformed plastically about 6% before fracture at stresses which are about one-quarter of reported polycrystalline fracture strengths. The macroscopic yield drops apparently exponentially from an extrapolated val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1963
1963
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 5 publications
0
22
1
Order By: Relevance
“…Hulse and Pask have shown that MgO single crystal can deform plastically down to very low temperatures, measuring a fracture strain of about 6% at 77 K [14]. Surface analyses emphasize 90 • shear bands that confirm the joint activity of two conjugate 1 ⁄2<110>{110} slip systems as already observed in Day and Stokes' work [7].…”
Section: Strain Hardening In Mgo Single Crystalmentioning
confidence: 50%
See 3 more Smart Citations
“…Hulse and Pask have shown that MgO single crystal can deform plastically down to very low temperatures, measuring a fracture strain of about 6% at 77 K [14]. Surface analyses emphasize 90 • shear bands that confirm the joint activity of two conjugate 1 ⁄2<110>{110} slip systems as already observed in Day and Stokes' work [7].…”
Section: Strain Hardening In Mgo Single Crystalmentioning
confidence: 50%
“…Strain-hardening rates were also computed and show a satisfactory agreement with experiments [8,14,44] at 1000 K and 2000 K for both slip modes. Again, no multi-mode configurations between slip modes were investigated.…”
Section: Grain-scale Deformation: On the Role Of Temperature On Mgo Smentioning
confidence: 63%
See 2 more Smart Citations
“…No stress-strain curves have been taken at lower temperatures, but the brittle-to-ductile transitions in ionic crystals are usually fairly gradual. 14,15 In addition, local plastic flow may occur even if the material does not exhibit macroscopic yield, as evidenced by recent work on germanium. 16 Thus it is reasonable to suppose that plastic flow accounts for the observed thickness dependence and scatter in electric strength at −80°C and that it would cause an even larger effect at −195°C except that fracture occurs first.…”
Section: Resultsmentioning
confidence: 99%